THE MICROSTRUCTURAL PROPERTIES OF PLASTER COMPOSITE PRODUCED DURING PRE-REPUBLIC AND EARLY REPUBLIC PERIODS IN DEMIRCI - Yıldızel, SadıkAlper (International Journal of Engineering Technologies and Management Research, 2017)
Structural plaster properties of the residence type buildings that were constructed during prerepublic and early republic periods in Demirci were investigated within the scope of this study. Samples taken from the existing structures were dried in laboratory conditions and made ready for micro-structure examination. Proper samples were examined with scanning electron microscopy (SEM) with the sensitivity of 5 nm and a magnification of 20.000 times, and the optical microscope (magnification: 250 x). In the light of obtained results, it has been determined that the microstructure of the composite used in the Demirci county in the preRepublican period and early republic period is similar to the resultant of mixes produced with the modern fiber added composite production technology. It is thought that this study will contribute to the study of the production of the related building materials to be improved in the future within the limits of the district.